Tinjauan Yuridis terhadap Penanganan Dugaan Pelanggaran Administrasi dalam Pemilihan Bupati dan Wakil Bupati Aceh Timur Tahun 2024 - Teuku Muhammad Hafizh; Tamaulina Br. Sembiring (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2026)
Alleged administrative violations in the 2024 East Aceh Regent and Deputy Regent election involving village heads and village officials raise issues regarding the mechanisms for handling violations and the evidentiary standards applied in resolving election result disputes. This study aims to analyze the mechanisms employed by the Election Supervisory Committee (Panwaslih) to handle alleged administrative violations and the evidentiary considerations found in Constitutional Court Decision Number 44/PHPU.BUP-XXIII/2025. A normative-juridical method was utilized, incorporating both statutory and case-based approaches. The findings indicate that alleged violations must be supported by sufficient evidence, meet legal criteria, and be proven to have significantly influenced the election outcome. The effectiveness of electoral justice relies on timely reporting, robust evidence, transparent handling, and a clear distinction between procedural violations and disputes over election results.